To solve the system of linear equations given:
- \( 4h + 4s = 10 \)
- \( 7h + 5s = 15 \)
We can simplify the first equation by dividing everything by 4:
\[ h + s = 2.5 \quad \text{(Equation 1)} \]
Now we rearrange Equation 1 to express \( s \) in terms of \( h \):
\[ s = 2.5 - h \quad \text{(Equation 3)} \]
Next, we can substitute Equation 3 into the second equation (Equation 2):
\[ 7h + 5(2.5 - h) = 15 \]
Distributing the 5 in the equation:
\[ 7h + 12.5 - 5h = 15 \]
Now, combine like terms:
\[ 2h + 12.5 = 15 \]
Subtract 12.5 from both sides:
\[ 2h = 2.5 \]
Now divide by 2:
\[ h = 1.25 \]
Now that we have the value of \( h \), substitute it back into Equation 3 to find \( s \):
\[ s = 2.5 - h = 2.5 - 1.25 = 1.25 \]
Thus, the costs are:
\[ h = 1.25, \text{and} , s = 1.25 \]
In decimal form:
- \( h = $1.25 \)
- \( s = $1.25 \)
Final answers: \[ h = 1.25 \quad s = 1.25 \]